The world is your office : how work from anywhere boosts talent, productivity, and innovation - Choudhury, Prithwiraj (Harvard Business Review Press, 2025)
"In recent years, companies in a wide range of industries have adopted radically flexible work policies that allow employees and teams to work from anywhere (WFA), untethered to a physical office. The leaders at these companies understand that geographic flexibility is a competitive advantage: a way to attract and retain high-quality and diverse talent at a global scale. If other companies want to find and keep the very best talent, they must embrace WFA. In The World Is Your Office, Harvard Business School professor Prithwiraj Choudhury takes readers inside the companies at the forefront of this growing phenomenon-from startups to bigger, more traditional organizations-while offering leaders a playbook for implementing a variety of WFA policies they can tailor to their own needs. This includes: Using WFA as a means of hiring and retaining the best talent in your field; best practices for meeting the challenges of managing a WFA team or workforce, including ways to build community, improve communication, and share knowledge; understanding how AI and automation are extending WFA to manufacturing and other deskless settings; and case studies of companies that have implemented WFA to great effect. Filled with smart insights and in-depth examples, and inspired by a decade's worth of pioneering research, The World is Your Office will help leaders attract superior talent, boost innovation, and improve productivity and diversity"--